Recognizing sponge in Spongiostroma Gürich, 1906 from the Mississippian of Belgium. (January 2023) - Lee, Jeong-Hyun; Riding, Robert
Abstract: Spongiostroma Gürich, 1906 from the Mississippian of Belgium was initially provisionally placed in Foraminifera and subsequently compared with hydrozoans and microbial carbonates. For nearly 100 years, the term spongiostromate has been widely applied to clotted microbial fabrics in stromatolites and oncolites. Examination of the type material shows that S. mæandrinum Gürich, 1906, the type species of Spongiostroma, consists of numerous juxtaposed millimetric pillow-like masses permeated by thin anastomose sparry microscopic fibers (vermiform fabric) in fine-grained groundmass, locally traversed by millimetric rounded to elongate partly sediment-filled openings. Here we interpret S. mæandrinum to be a lobate sponge composed of mammiform papillae formed by calcified spongin network and traversed by canals and spongocoel. These are typical features of calcified remains of keratosan demosponges. We redescribe and revise S . mæandrinum and interpret it as a keratosan demosponge with papilliform morphology. This upholds Gürich's (1906 ) initial opinion that Spongiostroma could be a sponge and supports suggestions that keratosan vermiform fabric has long been confused with microbial carbonate. Since S . mæandrinum is not a stromatolite, it is inappropriate to use the term spongiostromate to describe microbial carbonate microfabric.